2021
DOI: 10.1155/2021/8822069
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson’s Disease Diagnosis in Cepstral Domain Using MFCC and Dimensionality Reduction with SVM Classifier

Abstract: Parkinson’s disease (PD) is one of the most common and serious neurological diseases. Impairments in voice have been reported to be the early biomarkers of the disease. Hence, development of PD diagnostic tool will help early diagnosis of the disease. Additionally, intelligent system developed for binary classification of PD and healthy controls can also be exploited in future as an instrument for prodromal diagnosis. Notably, patients with rapid eye movement (REM) sleep behaviour disorder (RBD) represent a go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 49 publications
1
14
0
2
Order By: Relevance
“…Our study is therefore the first one to provide a thorought classification of voice in PD patients, according to the stage (i.e., de novo ) and severity of the disease as well as the effect of chronic L-Dopa treatment. Also, supporting the biological plausibility of our results, the most relevant voice features selected by our machine learning algorithms (among the large dataset of features examined), include those previously identified by spectral analysis such as the fundamental frequency ( 3 , 12 16 , 26 , 45 ). Moreover, our study showed for the first time significant clinico-instrumental correlations: the higher LR values attributed by machine learning, the longer the disease duration, the higher severity of motor symptoms, and finally the greater voice impairment in patients with PD.…”
Section: Discussionsupporting
confidence: 80%
“…Our study is therefore the first one to provide a thorought classification of voice in PD patients, according to the stage (i.e., de novo ) and severity of the disease as well as the effect of chronic L-Dopa treatment. Also, supporting the biological plausibility of our results, the most relevant voice features selected by our machine learning algorithms (among the large dataset of features examined), include those previously identified by spectral analysis such as the fundamental frequency ( 3 , 12 16 , 26 , 45 ). Moreover, our study showed for the first time significant clinico-instrumental correlations: the higher LR values attributed by machine learning, the longer the disease duration, the higher severity of motor symptoms, and finally the greater voice impairment in patients with PD.…”
Section: Discussionsupporting
confidence: 80%
“…The second dataset is also multiple types of voice phonations dataset. The dataset was collected by Rahman et al [50] in Lady Reading Hospital (Medical Teaching Institution), Pakistan. The dataset is a relatively bigger dataset and was collected from 160 subjects out of which 60 subjects belong to PD class and the remaining 100 subjects are from the healthy class.…”
Section: Multiple Types Of Vowel Phonation Datasetsmentioning
confidence: 99%
“…For classification purposes, they developed an SVM model with different types of kernels and obtained PD detection accuracy of 87.5% accuracy using LOSO CV [19]. Recently, Rahman et al [50] collected a relatively bigger dataset and showed that high PD detection accuracy on a bigger dataset is a challenging task. Most recently, Ali et al showed that instead of selecting features from multiple types of voice data, improved performance can be obtained by selecting samples before feature selection [13].…”
Section: Introductionmentioning
confidence: 99%
“…Our mechanized ML approach permits complex prescient models to be reproducible and available to the local area. Shahid and Singh [65] proposed a PCA based profound neural organization (DNN) model to foresee Motor-UPDRS and Total-UPDRS in Parkinson's illness (PD) movement. The model utilized the decreased info highlight space of Parkinson's telemonitoring dataset for checking the movement.…”
Section:  Issn: 2502-4752mentioning
confidence: 99%